THE EFFECTIVENESS OF INTERACTIVE-MULTIMEDIA-AIDED SO-CIAL COGNITIVE MODEL FOR EARLY READING LEARNING IN ELEMENTARY SCHOOL - Indah Nurmahanani; Yeti Mulyati; Andoyo Sastromiharjo (Universitas Negeri Makassar, 2021)
This study aimed to measure the effectiveness of interactive multimedia aided social cognitive model in early reading learning, implemented to improve students’ early reading skills. The model was implemented to 195 first- and second-graders in an elementary school in Bandung. Descriptive statistics analysis was conducted to measure the difference in students’ ability before and after the treatment, based on the result of pre- and post-test using EGRA instrument. Results of this study indicated that social cognitive learning could be combined with interactive multimedia to effectively improve students’ early reading ability. However, further study is required to understand why the model contributed lower significance towards improvement of word-reading skill than towards improvement of other aspects of early reading skills.